ANALISIS HAMBATAN GURU DALAM PENERAPAN PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Geliya Zuliyanti; Sinta Astrimelda; Nur Zahra; M Iqbal Arrosyad (CV. ADIBA AISHA AMIRA, 2025)
This research is based on the ineffectiveness of thematic learning implementation at the elementary school level due to various challenges faced by teachers. The purpose of this study is to identify the challenges experienced by teachers in implementing thematic learning in elementary schools. The method used in this study is qualitative with the research objects being classroom teachers in elementary schools that implement thematic learning. This research was conducted at SD Negeri 2 Simpang Katis in October 2025. Data collection techniques included in-depth interviews, documentation, and direct observation in the classroom. Data analysis was carried out using data reduction techniques, data presentation, and inductive conclusion drawing. The results of the study indicate several significant inhibiting factors, including limited learning resources, lack of training for teachers on thematic learning, ineffective time management, and minimal support from the school and parents. These challenges make it difficult for teachers to plan and implement thematic learning optimally. Recommendations are given for improving teacher training and providing appropriate learning resources to support the success of thematic learning in elementary schools.